A COMBINATORIAL IDENTITY AND THE FINITE DUAL OF INFINITE DIHEDRAL GROUP ALGEBRA. Issue 2 (13th March 2021) - Ge, Fan; Liu, Gongxiang
Abstract: In this paper, we find a combinatorial identity which is related to the multi‐dimensional integral γ m in the study of divisor functions (see (1)). As an application, we determine the finite dual of the group algebra of infinite dihedral group.